Ethics and drug development - Lenk, Christian (Henry Stewart Talks, 2022)
Ethical framework for clinical research, Research Ethics Committees (RECs), RECs: Ethical, legal and scientific review, Ethics and research design, Randomisation, blinding and placebo control, Vulnerable patient groups, Challenges in the COVID-19 pandemic, Patient safety